Improvement of Guideline Adherence After the Implementation of an Antibiotic Stewardship Program in a Secondary Care Pediatric Hospital - Metz, Jakob; Oehler, Philipp; Burggraf, Manuela; Burdach, Stefan; Behrends, Uta; Rieber, Nikolaus (Frontiers in Pediatrics, 2019)
Introduction The accelerating threat of multidrug-resistant bacteria forces health care providers to use antibiotics more rationally. Antibiotic stewardship programs (ASP) are a proven and safe way to achieve that goal. They have been comprehensively studied in adults but data from secondary care pediatric hospitals are lacking. Material and Methods In our study an ASP with standard operating procedures (SOPs), audits, a weekly ward round with experts in pediatric infectious diseases and an antibiotic pocket-card for selected infectious diseases was established in July 2017 in a Munich municipal secondary care children’s hospital. All antibiotic prescriptions on general pediatric wards were reviewed each in the first quarter of 2017 and 2018. The primary outcome was adherence to treatment guidelines. Secondary outcomes were substance consumption, duration of therapy and death. Results After the ASP was implemented guideline adherence increased significantly from 33% to 63%. The consumption of cephalosporins decreased significantly (-60%), whereas aminopenicillin use increased accordingly (+120%). Neither in the pre- nor in the post-intervention group deaths occurred. Discussion Data on ASP in pediatric secondary care hospitals are scarce. Most previous studies have been performed at tertiary care / university children’s hospitals. We demonstrate a significant improvement in guideline adherence regarding antibiotic treatments after the implementation of an ASP. Cephalosporin consumption decreased which might be relevant for the selection of multidrug-resistant bacteria (e.g. vancomycin-resistant enterococci). Results are limited by the single-center design and the short observation period. The study encourages the implementation of ASPs in secondary care children’s hospitals.